Performance measures for the SACRED team-centered approach to advanced gastrointestinal endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Quality Improvement Initiative - Ching, Hey-Long; Lau, Michelle S.; Azmy, Iman A.; Hopper, Andrew D.; Keuchel, Martin; Gyökeres, Tibor; Kuvaev, Roman; Macken, Elisabeth J.; Bhandari, Pradeep; Thoufeeq, Mo; Leclercq, Philippe; Rutter, Matthew D.; Veitch, Andrew M.; Bisschops, Raf; Sanders, David S. (Endoscopy, 2022)
The European Society of Gastrointestinal Endoscopy and United European Gastroenterology have defined performance measures for upper and lower gastrointestinal, pancreaticobiliary, and small-bowel endoscopy. Quality indicators to guide endoscopists in the growing field of advanced endoscopy are also underway. We propose that equal attention is given to developing the entire advanced endoscopy team and not the individual endoscopist alone.We suggest that the practice of teams intending to deliver high quality advanced endoscopy is underpinned by six crucial principles concerning: selection, acceptance, complications, reconnaissance, envelopment, and documentation (SACRED).